Job Satisfaction and Its Determinants among School Nurses - Tuitui, Roshani Laxmi; Rai, Bala; Thapa Pachya, Ambika; Pokharel, Kritagya (Journal of Nepal Health Research Council, 2025)
Background: School nurses play a crucial role in promoting health and well-being among students. In Nepal, the school nursing program in public school started since five years and there is a need for a study on their job satisfaction. Therefore, this study aims to investigate the job satisfaction and its determinants among school nurses in Nepal.Methods: A descriptive cross-sectional study was conducted among 1011 school nurses working in public schools from all provinces in Nepal. The study utilized Paula L. Stamp’s modified Index of Work Satisfaction, assessing six domains: pay, autonomy, task requirements, organizational policy, professional status, and interaction. Data were collected through a questionnaire distributed electronically; bivariate and multivariate logistic regression were used to find out determinants.Results: All school nurses were approached, but only 545 (53.9%) participated. Among them 51.7% expressed overall job satisfaction. Among the six domains, the highest job satisfaction was observed in the professional status (85.3%), interaction (72.8%), and task (61.8%) component while the lowest was in the pay (3.7%) component. Logistic regression revealed the significant determinants were working solely as school nurse (0.001), bachelor and above academic qualification (0.031) and family type p= absent in bot “working solely as school nurse (0.001), bachelor and above academic qualification (0.031).Conclusions: School nurses with minimum bachelor degree, has better job satisfactions. Similarly, the program implementer needs attention to enhance pay for school nurses and allow autonomy in workplace to increase job satisfaction.Keywords: Job satisfaction; Nepal; school nurses; school nurse program